Gambaran Faktor Resiko Penyakit Tidak Menular (PTM) Pada Mahasiswa Sekolah Tinggi Ilmu Kesehatan Bantul - Dian Novita Kumalasari; Erma Pranawati; Supatmi; Eni Purwaningsih; Siti Hanifatun Fajriah (Badan Perencanaan Pembangunan Daerah Kabupaten Bantul, 2025)
Non-communicable diseases (NCDs) among adolescents have become a major concern in global public health, particularly due to their increasing prevalence and impact on quality of life. Adolescents today are exposed to a variety of risk factors that contribute to the development of NCDs, such as unhealthy lifestyles and risky behaviors that begin early in life. These factors include tobacco use, poor dietary habits, lack of physical activity, and alcohol consumption. The objective of this study is to identify early risk factors for NCDs among students of STIKES Bantul. This study is a descriptive observational research using a cross-sectional design. Data were analyzed univariately by presenting the distribution and frequency of each variable. The results show that the majority of respondents were 19 years old (29,5%), and most were female, totaling 53 individuals (86,9%). Most respondents had a normal Body Mass Index (BMI), accounting for 75,4%, while the majority of students had normal blood pressure (98.4%). Furthermore, most respondents engaged in moderate physical activity (57,4%). The majority also had normal stress levels (52,5%), and 91,8% of respondents were non-smokers. The overview of risk factors for non-communicable diseases at STIKES Bantul indicates that the overall level is still very low; however, a small proportion of respondents have a risk of developing non-communicable diseases due to being overweight or obese based on BMI, low levels of physical activity, and moderate stress levels.